فقہ حنفی اور فقہ جعفری کے مناہجِ اجتہاد:ایک مطالعہ (Al-Qamar, 2019)
Companions of the Prophet of Islam who endowed with Ijtihād abilities guided the Muslim community in Sharīʻah related issues. After the companions, different Muslim Jurists presented solutions to the problems of their times. This article studies the methodologies of Ijtihād in Ḥanafī and Jaʻfarī schools of law. It finds that to all jurists, Quran and Sunnah are the main sources of law. Jurists of both the schools are also in agreement regarding Ijmāʻ. However, according to the Ḥanafīs, the fourth source is Qiyās and to the Jaʻfarīs ʻql. Qiyās and ʻql are basically the same things. Thus the study shows that, in spite of some differences, both the schools are very close to each other in terms of methodology of Ijtihād. It also makes clear that Islam is not a static religion; Muslim Jurists having the qualification of Ijtihād can solve the Sharīʻah related problems of Muslim community in all the eras and circumstances.
Keywords: Ijtihād; jurisprudence; Ḥanafī; Jaʻfarī; methodology